Morphological and biochemical reaction of rice cultivars to Rhizoctonia solani - Haque, Ziaul; Khan, Mujeebur Rahman Khan; Singh, Reshu (Indian Journal of Plant Protection, 2020)
In the present study, 18 rice cultivars were evaluated for host reaction to sheath blight fungus, Rhizoctonia solaniv under pot conditions. The host reaction was evaluated on the basis of biochemical viz., total phenol contentsv(TPC) and salicylic acid contents (SAC) and morphological characters viz., sheath blight index, plant yieldnband soil population of R. solani. Among 18 rice cultivars, Samba Mahsuri, Vivekdhan and JKRH401 expressed tolerance against the test fungus. The cvs. PS-5 and PS-4 were found highly susceptible to sheath blight. The greatest increase in the leaf contents of salicylic acid (13-16%) and total phenol (15-19%) was recorded in the cv. Santhi which expressed resistance to R. solani and exhibited lowest decrease in the yield. The TPC and SAC of leaves increased up to 15 days of planting, and thereafter, decreased gradually. Increase in the TPC and SAC was negatively correlated with the disease severity. Based on the morphological and biochemical host reaction, cv. JKRH401 and Santhi expressed tolerance to a level that may be exploited for commercial cultivation of rice in the areas infested with sheath blight fungus. The cvs. PS-5 and PS-4 should be avoided in the sheath blight infested area/field because of their higher deg ee of susceptibility to R. solani.